Proceedings of the 1st Annual International Conference on Mathematics, Science, and Education (ICoMSE 2017) 2018
DOI: 10.2991/icomse-17.2018.28
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Inquiry-Based Learning Module to Improve the Cognitive Learning Outcomes

Abstract: The needs of the 21st century in education need the creating of young people to have life skills. The life skills can be trained through the learning process and identified through student learning outcomes. Learning outcomes are one of the factors in successful learning. Therefore, a solution is needed to optimize student learning outcomes in the learning process by using the teaching material in the form of the module. The objective of this research is to know the effectiveness of inquirybased learning modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…It has been found that students who experience hands-on activities find the learning content more enjoyable and relevant (Suduc et al, 2015). Inquiry-based learning also improves student learning outcomes (Wang et al, 2015;Tawfik et al, 2020;Anjani et al, 2018). Eltanahy and Forawi (2019) found that students have positive attitudes towards inquiry-based activities in science classrooms and therefore show more interest in learning about science, although this needs to be guided to some extent by the teacher (Szalaya, et al, 2021).…”
Section: Inquiry-based Learningmentioning
confidence: 99%
“…It has been found that students who experience hands-on activities find the learning content more enjoyable and relevant (Suduc et al, 2015). Inquiry-based learning also improves student learning outcomes (Wang et al, 2015;Tawfik et al, 2020;Anjani et al, 2018). Eltanahy and Forawi (2019) found that students have positive attitudes towards inquiry-based activities in science classrooms and therefore show more interest in learning about science, although this needs to be guided to some extent by the teacher (Szalaya, et al, 2021).…”
Section: Inquiry-based Learningmentioning
confidence: 99%
“…This is line in with [18] expression that the inquiry learning model is more effective than the conventional model. Inquiry-based learning used in the learning process can improve student learning outcomes because in the learning process structured activities are presented in the form of practicums and observations using inquiry-based learning [19][20]. Inquiry-based learning contains learning activities encourage students to analyze, solve problems based on facts found and designed to obtain students' conceptual understanding.…”
Section: Fig 1 Data Analysis Of Student Physics Learning Outcomes Onmentioning
confidence: 99%
“…Perbedaan hasil pretest dan posttest tersebut menunjukkan bahwa hasil belajar meningkat setelah dilakukan pembelajaran dengan menggunakan modul pembelajaran dengan pendekatan inkuiri. Hal ini membuktikan bahwa pembelajaran dengan menggunakan modul efektif untuk meningkatkan hasil belajar(Anjani, Suciati, & Maridi, 2017).SIMPULAN Modul aljabar linier dan matriks telah disusun berdasarkan tahapan Dick & Carey, meliputi tahap analisis kebutuhan, analisis instruksional, analisis mahasiswa dan konten, menulis tujuan kinerja, pengembangan instrumen penilaian, pemilihan strategi pembelajaran, mengembangkan dan memilih bahan instruksional, merancang dan melakukan evaluasi formatif instruksi, revisi hingga…”
unclassified